1998
DOI: 10.1183/09031936.98.11051043
|View full text |Cite
|
Sign up to set email alerts
|

Secretory component production by human bronchial epithelial cells is upregulated by interferon gamma

Abstract: The respiratory tract in humans represents a large mucosal area exposed to the environment. The secretory immune system is the first, noninflammatory line of defence, protecting the respiratory tract from viral and bacterial infections. Secretory immunoglobulin A (S-IgA) is the major immunoglobulin present in human airway secretions [1]. The humoral secretory immune response depends on interactions between the B-cell system for the production of J-chain-containing polymeric IgA (pIgA) and the mucosal epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…We suggest the difference lay in their use of cell lines or culture conditions in which SC is expressed at low levels. For example, the A549 cell line used by Smart and Casale (36) expresses SC at levels three orders of magnitude less than primary epithelial cells (25). Second, the culture of primary bronchial epithelial cells on uncoated plastic, for example by Abdelaziz et al (37), reduces SC expression by 30-fold compared with growth on collagen-coated plastic as shown by Fiedler et al (28).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We suggest the difference lay in their use of cell lines or culture conditions in which SC is expressed at low levels. For example, the A549 cell line used by Smart and Casale (36) expresses SC at levels three orders of magnitude less than primary epithelial cells (25). Second, the culture of primary bronchial epithelial cells on uncoated plastic, for example by Abdelaziz et al (37), reduces SC expression by 30-fold compared with growth on collagen-coated plastic as shown by Fiedler et al (28).…”
Section: Discussionmentioning
confidence: 84%
“…In cultures of primary human bronchial epithelial cells isolated from enzymatic digests of segments of bronchial tubes from patients with a history of smoking and mild chronic obstructive pulmonary disease undergoing lobectomy for lung cancer, Godding et al (25) reported 15 times lower SC release. Because decreased Clara cell protein (CC10) levels have been measured in epithelial cells from smokers (26), it is possible that synthesis of other proteins such as SC may be similarly altered.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ include ICAM-1 expression (27), specific lectin-binding activity (28), and the absence of secretory component (29). As such they appear to be an acceptable surrogate for the basal AECs that are in direct contact with intraepithelial DCs in vivo.…”
Section: Hbe14omentioning
confidence: 99%
“…The epithelial expression of pIgR appears thus upregulated in vitro by different cytokines, especially by IFN-c both on intestinal epithelial cell lines [42] and the bronchial epithelial cell line Calu-3 [43], as well as on primary bronchial epithelial cells [44], by interacting with specific receptors expressed restrictively on the basolateral pole of these cells. Synergistically with IFN-c, IL-4 upregulates SC expression on HT-29 colon carcinoma cells [42] and Calu-3 cells [45], while the effects of these cytokines appeared additive on IgA transport.…”
Section: Immunoglobulin-a Transportmentioning
confidence: 99%